Democracia e imagens: representações políticas e artísticas - Bernardo Supranzetti de Moraes (2017)
This dissertation proposes a historical and philosophical examination of the concept of "democracy", to understand its true postulates and its meaning. Throughout the text, we explore the symbolic and axiological variations and tensions of the term over time, as well as the historical and political moments which stimulated democratic experiences. With the help of the arts to better understand these variations and tensions, the images emerge in this study sometimes as an expression, sometimes as a critique of the meanings and perceptions that are associated with democracy from Ancient Greece to the present day.